Analisis Faktor-Faktor yang Mempengaruhi Niat Pembelian Ulang pada Shopee dengan Kepuasan Pelanggan sebagai Variabel Mediasi - Ratnawati; Yudi Haliman; Sebastian (Department of Management - Institut Shanti Bhuana, 2022)
This study aims to analyze the factors that influence consumers' repurchase intentions at Shopee with visitor satisfaction as a mediating variable. This study uses a quantitative approach by collecting respondent data through a Google Form survey. The sampling technique used convenience sampling with a total of 102 respondents. The data analysis technique used a partial least squares structural equation model (PLS-SEM) which was tested using SmartPls 3.0. The results showed that delivery service, brand reputation, and cashback promos had a positive effect on customer satisfaction and had a positive effect on repurchase intentions. Customer satisfaction is a factor that mediates the relationship between service delivery and repurchase intentions, and the relationship between cashback promos and repurchase intentions.